Family entrepreneurship interaction between parents and children - Placido, Diana A.
This case study explored family dynamics as it relates to entrepreneurial traits, career aspirations and business succession. It was specifically geared towards identifying the entrepreneurial traits that were passed on from one generation to another, the roles that family members played in business decision-making, the influences of parent entrepreneurs in the career aspirations of their children, the issues concerning business succession and the strategies entrepreneurial homes utilized in dealing with business succession planning. The researcher used non-probability sampling procedure through purposive sampling. Five nuclear families engaged in various forms of enterprise or retail were selected as respondents for the study. Information was obtained through an in-depth interview from parents and their children. The data were analyzed using content analysis and descriptive statistics. The findings of the study revealed the list of entrepreneurial traits that were passed on by their parents to their children, the evident roles that children played in the business, the influences of the parents in the educational and occupational aspirations of their children. One disturbing result is that family business owners lack systematic plans of business succession. The entrepreneurial families fell short of strategies and techniques that may help them in dealing with family business succession planning. Through this study, policy-makers may help promote family business succession planning through the creation and approval of policies that will address the needs of family businesses. For Home Economics educators, they may include more topics on business succession in entrepreneurship courses to further the development and advancement of the discipline. The educators may also focus on cultivating entrepreneurial traits that are not typically passed on from one generation to the next though the enhancement of some components of the curriculum as the results of the study suggest.